Image of the Month: Enterocolitis Following a Pull-through for Total Colonic Hirschsprung Disease in a 2-Year-Old Boy - Apte, Anisha; McKenna, Elise; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2020)
We present a case of a 2-year-old boy with total colonic Hirschsprung disease (HD) who underwent an ileostomy as a newborn, and then colectomy and pull-through at 10 months of age. Since then he has presented four times with enterocolitis. The case is presented with a focus on evaluating patients with HD who present with obstructive symptoms following corrective surgery. A key image is presented along with questions formatted as a quiz to guide readers through critically evaluating the case.
Keywords: Hirschsprung disease; enterocolitis; pull-through